Detection of a novel astrovirus from a black-naped monarch (Hypothymis azurea) in Cambodia. Issue 1 (December 2015) - Mendenhall, Ian; Yaung, Katherine; Joyner, Priscilla; Keatts, Lucy; Borthwick, Sophie; Neves, Erica; San, Sorn; Gilbert, Martin; Smith, Gavin
Abstract Background Astroviruses are comprised of two genera withAvastrovirus infecting birds andMamastrovirus infecting mammals. Avastroviruses have primarily been associated with infections of poultry, especially chicken, turkey, duck, and guineafowl production systems, but also infect wading birds and doves. Outcomes result in a spectrum of disease, ranging from asymptomatic shedding to gastroenteritis with diarrhea, stunting, failure to thrive and death. Findings Virological surveillance was conducted in birds from two sites in Cambodia in 2010. Samples were screened for influenza, astroviruses, coronaviruses, flaviviruses, and paramyxoviruses. A total of 199 birds were tested and an astrovirus was detected in a black-naped monarch (Hypothymis azurea) . Conclusions This is the first astrovirus detection in a passerine bird. Phylogenetic analysis and nucleotide distances suggest that this avastrovirus forms a distinct lineage and may constitute a fourth avastrovirus group.